Phylogeographic patterns in Africa and high resolution delineation of genetic clades in the Lion (Panthera leo) - Bertola, L; Jongbloed, H; Van Der Gaag, K; De Knijff, P; Yamaguchi, N; Hooghiemstra, H; Bauer, H; Henschel, P; White, P; Driscoll, C; Tende, T; Ottosson, U; et al. (Springer Nature, 2016)
Comparative phylogeography of African savannah mammals shows a congruent pattern in which populations in West/Central Africa are distinct from populations in East/Southern Africa. However, for the lion, all African populations are currently classified as a single subspecies (Panthera leo leo), while the only remaining population in Asia is considered to be distinct (Panthera leo persica). This distinction is disputed both by morphological and genetic data. In this study we introduce the lion as a model for African phylogeography. Analyses of mtDNA sequences reveal six supported clades and a strongly supported ancestral dichotomy with northern populations (West Africa, Central Africa, North Africa/Asia) on one branch, and southern populations (North East Africa, East/Southern Africa and South West Africa) on the other. We review taxonomies and phylogenies of other large savannah mammals, illustrating that similar clades are found in other species. The described phylogeographic pattern is considered in relation to large scale environmental changes in Africa over the past 300,000 years, attributable to climate. Refugial areas, predicted by climate envelope models, further confirm the observed pattern. We support the revision of current lion taxonomy, as recognition of a northern and a southern subspecies is more parsimonious with the evolutionary history of the lion.